Ipod's Product Life Cycle / Intan Nur Haleeda Abdul Halim ... [et al.] - Abdul Halim, Intan Nur Haleeda; Zainal Rahmat, Fairuz Awatif; Wan Amin, Sharifah Sharina; Bachun, Amelda (2016)
iPod is a line of portable media players and multi-purpose pocket computers. Portable media player (PMP) is a device that stores and plays digital media, such as audio, images, and video files. The first version of iPod was released on 23 October 2001, while the latest version of iPod was released on 15 July 2015. Therefore, there are three current versions of the iPod. The first one is the ultra-compact iPod Shuffle. It was designed to be easily loaded with a selection of songs and to play them in random order and could hold up to 240 songs. The first generation of iPod Shuffle was announced on 11th January 2005, and the current fourth generation model was introduced on 1st September 2010. iPod Shuffle is the smallest model in Apple's iPod model and was the first iPod to use flash memory. Besides, the second version of iPod is the compact iPod Nano. This version of iPod also has four generations. The first generation was announced on 111 September 200, while the current fourth generation was released on 9 September 2008. iPod Nano is a small sized device with battery life up to 14 hours, while the screen was displaying 65,536 colors 4 GB capacities were available. Thus, the third version of iPod is the iPod Touch. This is the most popular of iPod model because it is a touchscreen-based version. It can be used as a music and video player, digital camera, handheld game device, and personal digital assistant (PDA). It connects to the Internet only through Wi-Fi base stations, does not use cellular network data, and is therefore not a smartphone, though it has a similar design to the iPhone and is often referred to as the "iPhone without a phone”.